Genetic Diversity and Population Structure of Genypterus chilensis, a Commercial Benthic Marine Species of the South Pacific - Córdova-Alarcón, Valentina R.; Araneda, Cristián; Jilberto, Felipe; Magnolfi, Piero; Toledo, María Isabel; Lam, Natalia (Frontiers in Marine Science, 2019)
The red cusk-eel (Genypterus chilensis, Guichenot 1848) is an iconic species in Chilean gastronomy, with a cultural significance that extends beyond its economic value, worthy of conservation. Despite the decline in fishery productivity across most of the distribution range for this species, little effort has been devoted to assessing stock management. In the present study, seven heterologous microsatellite loci (cmrGb3.8.1, cmrGb5.2B, cmrGb4.2A, cmrGb4.2B, cmrGb5.9, cmrGb4.11 and cmrGb2.6.1) were genotyped in a total of 153 individuals from four locations in central and southern Chile (30.5ºS–37.6ºS), comprising ~1000 km of coastline. Five microsatellite loci were consistently amplified with a low frequency of null alleles (<2.5%). These markers showed high average heterozygosity (HO=0.886 and HE=0.884) and PIC (0.869). Significant genetic differentiation among locations (global FST=0.043, global DJost=0.252) suggested the presence of at least three different genetic groups along the Chilean coast, with moderate levels of admixture between the two central populations (0.168 <Qmean<0.822). The southern population showed no admixture with the central populations (Qmean=0.985), less allelic richness and a small effective population size, indicating that urgent management measures must be developed for this fishery. The present study provides baseline information to assist fishery and aquaculture management, contribute to recovery of declining populations, promote sustainable fishing and aquaculture and avoid the collapse of red cusk-eel production.